EMOTIONAL POVERTY OF OLDER PERSONS IN RESIDENTIAL FACILITIES IN THE WESTERN CAPE PROVINCE OF SOUTH AFRICA - Human, Melanie; Slabbert, Ilze (Social Work/Maatskaplike Werk, 2025)
Older persons are often referred to as a forgotten generation even as the population is rapidly ageing worldwide. According to the World Health Organization, it is estimated that by 2030 one in every eight people will be over 65. A number of older persons regularly move to residential facilities owing to unforeseen circumstances such as deteriorating health. This study was conducted to explore the concept of the emotional poverty of older persons in residential facilities in the Western Cape province of South Africa. A qualitative approach was followed which was descriptive and explorative in nature. Purposive sampling was used to recruit and involve participants. Interviews were conducted with 20 older persons and 10 social workers. Data were verified by ensuring the credibility, authenticity, dependability and transferability of the study. The data were analysed and sorted into themes and sub-themes, with relevant narratives underpinning the themes and sub-themes. Findings of the study indicated that older persons in residential facilities often experience loneliness, depression and limited contact with the outside world, resulting in emotional poverty. Recommendations of the study include improved service rendering to reduce the emotional poverty of older persons.